2009
DOI: 10.1007/s00128-009-9765-x
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 Levels in Surk Samples, a Traditional Turkish Cheese from Southern Turkey

Abstract: In this study, aflatoxin M(1) (AFM(1)) contamination was investigated in Surk cheese, a traditional Turkish cheese consumed particularly in southern Turkey. For this purpose, 120 Surk cheese samples were collected from different retail markets and analysed by enzyme-linked immunoassay. The level of AFM(1) varied from 16 to 1,043 ng/kg in 72 of the Surk samples (60%), 16 of which (13.3% of 120 samples) contained AFM(1) amounts exceeding the maximum tolerance limit (250 ng/kg) established in Turkey. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several studies in different countries have reported high or low contamination levels of AFM1 in different categories of cheese samples (Aygun, Essiz, Durmaz, Yarsan, & Altintas, 2009;Kamkar, 2006;Manetta et al, 2009). These significantly variable AFM1 levels may be due to several influencing factors such as cheese manufacturing procedures and storage (Deveci, 2007), types of cheese, conditions of cheese ripening (Oruc, Cibik, Yilmaz, & Kalkanli, 2006), analytical methods and finally the geographical and seasonal effects (Tajkarimi et al, 2007(Tajkarimi et al, , 2008.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies in different countries have reported high or low contamination levels of AFM1 in different categories of cheese samples (Aygun, Essiz, Durmaz, Yarsan, & Altintas, 2009;Kamkar, 2006;Manetta et al, 2009). These significantly variable AFM1 levels may be due to several influencing factors such as cheese manufacturing procedures and storage (Deveci, 2007), types of cheese, conditions of cheese ripening (Oruc, Cibik, Yilmaz, & Kalkanli, 2006), analytical methods and finally the geographical and seasonal effects (Tajkarimi et al, 2007(Tajkarimi et al, , 2008.…”
Section: Resultsmentioning
confidence: 98%
“…Slightly higher efficiency results obtained by determining the soft cheese by ELISA method were expected since it is known that this method usually gives higher results compared with the confirmation methods (Aygun et␣al . 2009; Fallah et␣al . 2009), while the efficiency values obtained for semihard cheese were also expected, given the matrix influence of such a sample.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant problem caused by milk and dairy products in terms of AFM1 is that it is stable against heat process such as UHT, sterilization and pasteurization. This is the reason why AFM1 does not decrease in amount during the manufacture of dairy products [19]. Salted (tuzlu) yogurt, which is prepared by heating (second pasteurized at 90°C) of strained yogurt, is a traditional milk product that has a high amount of dry matter and long shelf-life [20,21].…”
Section: Introductionmentioning
confidence: 99%